BASICS OF PUBLIC SPEAKING - Novaković, Nataša; Teodosijević, Boris (BizInfo Blace, 2017)
Basics of public speaking is a work in which we emphasize the importance of mastering the techniques of public speaking and oratory skills, in order for that knowledge to serve each individual as a key tool for easier achievement of all objectives of business and personal communication. We explain and define the very concept of public speaking and its qualities and give an answer to the crucial question of who actually needs those oratory skills. Also, we turn to the basic divisions and types of speech, their main features and differences, as well as a very important segment of oratory which is improvised, or spontaneous speech.